Cyprus as an ancient hub for house mice and humans. (4th November 2018) - García‐Rodríguez, Oxala; Andreou, Demetra; Herman, Jeremy S.; Mitsainas, George P.; Searle, Jeremy B.; Bonhomme, François; Hadjisterkotis, Eleftherios; Schutkowski, Holger; Stafford, Richard; Stewart, John R.; Hardouin, Emilie A.
Abstract: Aim: The distribution of the western house mouse ( Mus musculus domesticus ) around the world has been strongly influenced by the movement of humans. The close association between the house mouse and human phylogeography has been primarily studied in the peripheral distribution of the species. Here, we inferred the complex colonization history of Cyprus, situated close to the centre of the house mouse distribution and one of the first European islands to be colonized by the species. We investigated the resulting complexity of house mouse population genetics as well as considering the value of the house mouse as a bioproxy for studying modern human movement. Location: The study was carried out on Cyprus. Methods: The analysis was performed using 221 new mitochondrial D‐loop sequences and assessed the fine‐scale population genetic structure using 18 autosomal microsatellite loci from 191 modern house mice specimens. Results: We found a high genetic variability in the island that is illustrated by the presence of individuals from 9 of the 11 previously identified house mouse haplogroups for the D‐loop, reflecting the hub‐like nature of the island to mice. Two main waves of mouse introductions were tentatively identified based on coalescent and mismatch analysis. The first is apparently related to the Bronze Age expansion and the second one to more recent human movements. Cyprus represents an island with high complexity due to different introductions related to human transport and activity. Main conclusions: The dispersal of mice along with humans has left a complex footprint on the island with two main waves of introductions suggested. The phylogeography of the house mouse on Cyprus is in concordance with the complex human colonization history of the island and validates the use of the house mouse as a proxy to study human migration.